Continuity of Hospital Care and Feeding Tube Use in Cognitively Impaired Hospitalized Persons. Issue 8 (13th May 2020) - Teno, Joan M.; Mitchell, Susan; Bunker, Jennifer; Meltzer, David; Gozalo, Pedro
Abstract : OBJECTIVES: Hospitalists are increasingly the attending physician for hospitalized patients, and the scheduling of their shifts can affect patient continuity. For dementia patients, the impact is unknown. DESIGN: Longitudinal study using physician billing claims between 2000 and 2014 to examine the association of continuity of care with the insertion of a feeding tube (FT). SETTING: US hospitals. PARTICIPANTS: Between 2000 and 2014, 166, 056 hospitalizations of patients with a prior nursing home stay, advanced cognitive impairment, and impairments in four or more activities of daily living (mean age = 84.2 years; 30.4% male; 81.0% white). MEASUREMENTS: Continuity of care measured at the hospital level with the Sequential Continuity Index (SECON; range = 0 to 100; higher score indicates higher continuity). RESULTS: Rates of a hospitalist acting as the attending physician increased from 9.6% in 2000 to 22.6% in 2010, whereas a primary care physician with a predominant outpatient focus acting as the attending physician decreased from 50.3% in 2000 to 12.6% in 2014. Post‐2010, a mixture of physician specialties increased from 55.5% to 66.4% with a reduction in hospitalists from 22.6% (2010) to 14.1% (2013). Continuity of care decreased over time with SECON dropping from 63.0 to 43.5. Adjusting for patient baseline risk factors, a nonlinear association was observed between SECON and FT insertion. Using cubic splines in the multivariate logistics regression model, the risk of FT insertion in hospitals where the SECON score dropped from 82 to 23 had an adjusted risk ratio (ARR) of FT insertion of 1.48 (95% confidence interval [CI] = 1.34‐1.63); hospitals in which SECON dropped from 51 to 23 had an ARR of FT insertion of 1.38 (95% CI = 1.27‐1.50). CONCLUSION: Hospitalized dementia patients in hospitals in which continuity of care was lower had higher rates of FT insertions. Newer models of care are needed to enhance care continuity and thus ensure treatment consistent with likely outcomes of care and goals of care. J Am Geriatr Soc 68:1852‐1856, 2020.